2012
DOI: 10.1063/1.4770464
|View full text |Cite
|
Sign up to set email alerts
|

Realistic performance prediction in nanostructured solar cells as a function of nanostructure dimensionality and density

Abstract: Charge-induced series resistance switching in GaAs solar cells AIP Advances 2, 042194 (2012) Schottky-barrier solar cell based on layered semiconductor tungsten disulfide nanofilm Appl. Phys. Lett. 101, 263902 (2012) Efficiency enhancement in mesogenic-phthalocyanine-based solar cells with processing additives APL: Org. Electron. Photonics 5, 274 (2012) Efficiency enhancement in mesogenic-phthalocyanine-based solar cells with processing additives Appl. Phys. Lett. 101, 263301 (2012) Improved performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Simulation results here are consistent with the results reported in literature. 177,178 Experimental study of InAs/GaAs QD-IBSC under light concentration has gradually drawn attention. 180 Takata et al have reported that in a well-developed cell, 181 a 50-layers stacked InAs/GaNAs QDSC with $15.7% efficiency at 1 sun has been shown to improve to efficiency of $20.3% at 100 suns and $21.2% at 1000 suns illumination.…”
Section: Concentrated Photovoltaic (Cpv) Characterizationmentioning
confidence: 99%
“…Simulation results here are consistent with the results reported in literature. 177,178 Experimental study of InAs/GaAs QD-IBSC under light concentration has gradually drawn attention. 180 Takata et al have reported that in a well-developed cell, 181 a 50-layers stacked InAs/GaNAs QDSC with $15.7% efficiency at 1 sun has been shown to improve to efficiency of $20.3% at 100 suns and $21.2% at 1000 suns illumination.…”
Section: Concentrated Photovoltaic (Cpv) Characterizationmentioning
confidence: 99%
“…where J is the current density, and the subscripts n and p indicate the electron and hole cases, respectively. For the bulk regions, the electron and hole concentrations are described in terms of the effective density of states (N c and N v ), conduction and valence band edge energies (E c and E v ), and quasi-Fermi levels (E Fn and E Fp ) [42]:…”
Section: Modeling and Simulationmentioning
confidence: 99%
“…[11][12][13][14][15] In another important point, highly dense QDs are needed to increase the power conversion efficiency. 16,17) Recently, we demonstrated in-plane ultrahigh-density InAs QDs with 0.5-1.0 × 10 12 cm −2 on a GaAsSb buffer layer and an InAsSb wetting layer (WL) on GaAs(001) substrates by molecular beam epitaxy (MBE). 15,[18][19][20] The heterostructure of these highdensity InAs QDs and GaAsSb buffer (or capping) layers forms the type-II band structure, in which electrons and holes are separated and confined, respectively, in the InAs QD level and the GaAsSb valence band.…”
Section: Introductionmentioning
confidence: 99%